Epigenetic modifications associated with genes implicated in cytokine storm: The potential biotherapeutic effects of vitamins and minerals in COVID‐19. Issue 5 (20th January 2022) - Muhammad, Aliyu; Forcados, Gilead Ebiegberi; Sani, Hadiza; Ndidi, Uche Samuel; Adamu, Auwal; Katsayal, Babangida Sanusi; Sadiq, Idris Zubairu; Abubakar, Yakubu Saddeeq; Sulaiman, Ibrahim; Abubakar, Ibrahim Babangida; Yusuf, Abdurrahman Pharmacy; Malami, Ibrahim; et al.
Abstract: Cytokine storm is a phrase used to refer to an abrupt upsurge in the circulating levels of various pro‐inflammatory cytokines, causing increased stimulation and activity of immune cells during disease conditions. The binding of pattern recognition receptors to pathogen‐associated molecular patterns during COVID‐19 infection recruits response machinery involving the activation of transcription factors and proteins required for a robust immune response by host cells. These immune responses could be influenced by epigenetic modifications as evidenced by significant variations in COVID‐19 pathophysiology and response to therapy observed among patients across the globe. Considering that circulating levels of interleukin 1, tumor necrosis factor‐α, and interleukin 6 are significantly elevated during cytokine storm in COVID‐19 patients, genetic and epigenetic variations in the expression and function of these proteins could enhance our understanding of the disease pathogenesis. Treatment options that repress the transcription of specific cytokine genes during COVID‐19 infection could serve as possible targets to counteract cytokine storm in COVID‐19. Therefore, the present article reviews the roles of cytokines and associated genes in the COVID‐19 cytokine storm, identifies epigenetic modifications associated with the disease progression, and possible ameliorative effects of some vitamins and minerals obtained as epigenetic modifiers for the control of cytokine storm and disease severity in COVID‐19 patients. Practical applications: COVID‐19 causes mortality and morbidity that adversely affect global economies. Despite a global vaccination campaign, side effects associated with vaccination, misconceptions, and a number of other factors have affected the expected successes. Cytokine storm in COVID‐19 patients contributes to the disease pathogenesis and response to therapy. Epigenetic variations in the expression of various cytokines could be implicated in the different outcomes observed in COVID‐19 patients. Certain vitamins and minerals have been shown to interfere with the expression and activity of cytokines implicated in cytokine storm, thereby counteracting observed pathologies. This review examines cytokines implicated in cytokine storm in COVID‐19, epigenetic modifications that contribute to increased expression of identified cytokines, specific foods rich in the identified vitamins and minerals, and suggests their possible ameliorative benefits. The article will be beneficial to both scientists and the general public who are interested in the role of vitamins and minerals in ameliorating COVID‐19. Abstract : The SARS‐CoV‐2 infection leads to NF‐κB‐mediated upregulation of pro‐inflammatory genes (the red ellipse) as well as the activation of mononuclear innate immune cells such as monocytes, macrophages, mast cells, natural killer cells, etc. to release inflammatory mediators, which ultimately leads to cytokine storm. Moreover, COVID‐19‐potentiated deficiency in micronutrients also causes the upregulation of ACE2 and some pro‐inflammatory genes (the black ellipse) via epigenetic mechanisms involving DNA hypomethylation, histone modifications, and chromatin remodeling, which exacerbate cytokine storm. This surge of inflammatory mediators leads to rapid recruitment of immune cells to infected tissues (particularly the lungs and other peripheral tissues) causing ARDS, pneumonia, and systemic tissue damages. Hence, reversal of the altered epigenetic changes by stimulating the chromatin‐modifying proteins (the green ellipse) with the appropriate combinations of vitamin and mineral supplements could be a promising therapeutic strategy in combating COVID‐19 cytokine storm.